2016
DOI: 10.1016/j.simyco.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

New Talaromyces species from indoor environments in China

Abstract: Talaromyces contains both asexual and sexually reproducing species. This genus is divided in seven sections and currently has 105 accepted species. In this study we investigated the Talaromyces isolates that were obtained during a study of indoor air collected in Beijing, China. These indoor Talaromyces strains are resolved in four sections, seven of them are identified as T. islandicus, T. aurantiacus, T. siamensis and T. albobiverticillius according to BenA sequences, while 14 isolates have divergent sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 37 publications
3
56
0
Order By: Relevance
“…They are generally congruent and could be obviously divided into three clades. Previous studies reported the Penicillium was polyphyletic and clade2 were Talaromyces species described as a sexual state of Penicillium [60,61]. In our results, the P. variabile HXQ-H-1 is mostly close to the T. islandicus WF-38-12, consistent with previous phylogenetic tree construction using ribosomal DNA [62,63].…”
Section: Phylogenetic Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…They are generally congruent and could be obviously divided into three clades. Previous studies reported the Penicillium was polyphyletic and clade2 were Talaromyces species described as a sexual state of Penicillium [60,61]. In our results, the P. variabile HXQ-H-1 is mostly close to the T. islandicus WF-38-12, consistent with previous phylogenetic tree construction using ribosomal DNA [62,63].…”
Section: Phylogenetic Analysissupporting
confidence: 91%
“…It's the first time Penicillium phylogenetic tree reconstructed by genome-wide sequence data. We found that the traditional morphological classification of Penicillium species was confusing, leading to polyphyletic classification [60,61]. Biological classification needs to correctly reflect the phylogenetic relationship and evolutionary trends.…”
Section: Phylogenetic Analysismentioning
confidence: 97%
“…The molecular taxonomy and nomenclature Talaromyces were comprehensively revised in the recent past (Houbraken and Samson et al 2011;Seifert et al 2012;Visagie and Jacobs 2012;Yilmaz et al 2012;Yilmaz et al 2014). Yilmaz et al (2014) resolved the phylogenetic positioning of Talaromyces species using a polyphasic taxonomic concept and placing 88 accepted species in seven well-defined sections, namely Bacillispori, Helici, Islandici, Purpurei, Subinflati, Talaromyces, and Trachyspermi. Subsequent to the monograph by Yilmaz et al (2014), 54 new Talaromyces species have been described from all over the world (Visagie et al 2015;Chen et al 2016;Luo et al 2016;Crous et al 2016;Romero et al 2016;Yilmaz et al 2016a, b;Crous et al 2017;Guevara-Suarez et al 2017;Peterson and Jurjević 2017;Wang et al 2017;Barbosa et al 2018;Su and Niu 2018;Jiang et al 2018;Varriale et al 2018).…”
Section: Morphology and Multigene Phylogeny Of Talaromyces Amyrossmanmentioning
confidence: 99%
“…The phylogenetic relationship of this strain with other section Helici members was studied by maximum likelihood (ML) and Bayesian inference (BI) analyses. A sequence alignment was made with the extracted sequences and the reference sequences of section Helici (Yilmaz et al 2014;Chen et al 2016) using MAFFT (Katoh et al 2005), and the optimal model was calculated in MEGA6 (Tamura et al 2013). A maximum likelihood (ML) tree was inferred with MEGA6, and the Bayesian inference (BI) analysis was performed in MrBayes 3.2.2 (Ronquist et al 2012).…”
Section: Methodsmentioning
confidence: 99%